TRANSLATION TECHNIQUES AND ACCURACY OF REPRESENTATIVE SPEECH ACTS IN GOING SEVENTEEN SUBTITLE - Denise Thea Maresca Rumekso; Septina Indrayani (LinguAmerta, 2024)
This study explores the translation techniques and accuracy of subtitles in the variety web series Going Seventeen, concentrating on representative speech acts in the "Bad Clue" segment. Using a descriptive qualitative method, the research delves into how these speech acts are translated and their effects on audience comprehension. As variety web series on platforms like YouTube become increasingly popular, effective subtitle translation is vital for bridging linguistic and cultural gaps. The study identified 120 sentences containing representative speech acts, with informing and asserting being the most prevalent, comprising 36% and 33% of the data, respectively. Less frequent acts, such as implying and reporting, enhance the dialogue's depth and engagement. The predominant translation techniques—literal translation, modulation, transposition, and established equivalents—contribute to the accuracy and clarity of the subtitles. Despite these techniques, the overall translation accuracy is moderate or less accuracte, with an average score of 2.56 out of 3, indicating some inaccuracies that affect the intended meaning and emphasis of the speech acts. These insights are crucial for improving subtitle translation practices and enhancing the global audience's understanding of digital content.